Methods & Measures - MIDWEST SAPH 2018 (University of Minnesota Libraries Publishing, 2018)
Article 1: QUALITY Makes No Sense without "U" and "I": Building Consensus around Quality via a Modified Delphi Process Robert A. Bechtol, MS; Kristin K. Janke, PhD Article 2: Theoretical and Empirical Analysis of Alternative Scoring Functions for the EQ-5D-5L Ruixuan Jiang, PharmD; You-Shan Feng, PhD; Thomas Kohlmann, PhD; A. Simon Pickard, PhD Article 3: Is Self-Rated Health of Americans Different in 2017 Compared to 2002? Ashley S. Cha, BA; Ernest H. Law, PharmD; James W. Shaw, PharmD, PhD; A. Simon Pickard, PhD Article 4: Development of an Instrument to Assess Academic Detailer's Experience with Academic Detailing Visits Christopher D. Saffore, PharmD; Andrea Monteiro, MSc; Mary Smart, PharmD; Aleksandrina Ruseva, PharmD Candidate; A. Simon Pickard, PhD; Todd A. Lee, PharmD, PhD Article 5: Development of an Instrument to Assess Prescriber's Satisfaction with an Academic Detailing Intervention Andrea L. Monteiro, MSc; Christopher D. Saffore, PharmD; Mary Smart, PharmD; Sarette Tilton, PharmD Candidate; Todd A. Lee, PharmD, PhD; A. Simon Pickard, PhD Article 6: Medication Hoarding Behaviors Scale (MHBS) SuHak Lee, PharmD; Donald L. Uden, PharmD